PERENCANAAN STRATEGI PEMASARAN DALAM PELUNCURAN PRODUK BARU DENGAN MEREK “EXO COFFEE” PADA PT. JAMU PUSPO INTERNUSA - Windu Mukti Winahyu; Efendi Tjendera; Reuben E. Gutierrez; Jimmy Sadeli (Bina Nusantara University, 2008)
Nowadays business rivalry going tightly and push the company to planning innovative marketing strategy. Speedy business world change situation in this globalization era will affecting successes level for a company in the past was not guaranteed the successes in the future. In order to compete and hold out, focusing activity and company business process have to concentrate in dynamic customers needs until purpose of filled customers needs and customers satisfaction will completed. Because of that historical background, we choose Group Field Project at PT. Jamu Puspo Internusa. The purpose that Group Filed Project want to achieve are to give more innovative marketing strategy based on society dynamic changes to arrogate and defend the EXO COFFEE market. Analyze and information obtained and limited in Jakarta and nearly area. Kind of research is doing by giving questioner and sample product to 300 responder. Result and conclusion from these researches are about information of consumer behaviors concerning to instant coffee products and information about strengthen and weakness of EXO COFFEE product see based on current marketing concepts. And the end, based on received and refined data, we conclude that a strategic marketing planning will arrogate market, brand awareness and market educated from EXO COFFEE special quality.